Critical Role of Hepatic Cyp450s in the Testis-Specific Toxicity of (5R)-5-Hydroxytriptolide in C57BL/6 Mice - Yu, Cunzhi; Li, Yu; Liu, Mingxia; Gao, Man; Li, Chenggang; Yan, Hong; Li, Chunzhu; Sun, Lihan; Mo, Liying; Wu, Chunyong; Qi, Xinming; Ren, Jin (Frontiers in Pharmacology, 2017)
Low solubility, tissue accumulation, and toxicity are chief obstacles to developing triptolide derivatives, so a better understanding of the pharmacokinetics and toxicity of triptolide derivatives will help with these limitations. To address this, we studied pharmacokinetics and toxicity of (5R)-5-hydroxytriptolide (LLDT-8), a novel triptolide derivative immunosuppressant in a conditional knockout (KO) mouse model with liver-specific deletion of CYP450 reductase. Compared to wild type (WT) mice, after LLDT-8 treatment, KO mice suffered severe testicular toxicity (decreased testicular weight, spermatocytes apoptosis) unlike WT mice. Moreover, KO mice had greater LLDT-8 exposure as confirmed with elevated AUC and Cmax, increased drug half-life, and greater tissue distribution. γ-H2AX, a marker of meiosis process, its localization and protein level in testis showed a distinct meiosis block induced by LLDT-8. RNA polymerase II (Pol II), an essential factor for RNA storage and synapsis in spermatogenesis, decreased in testes of KO mice after LLDT-8 treatment. Germ-cell line based assays confirmed that LLDT-8 selectively inhibited Pol II in spermatocyte-like cells. Importantly, the analysis of androgen receptor (AR) related genes showed that LLDT-8 did not change AR-related signaling in testes. Thus, hepatic CYP450s were responsible for in vivo metabolism and clearance of LLDT-8 and aggravated testicular injury may be due to increased LLDT-8 exposure in testis and subsequent Pol II reduction.